Degradation of Azoic congo red dye by using ultrasonic irradiation with additive - Nur Zainaim, Mohamed Nawi (2010)
The pollution due to textile dye effluents has been a major concern and the investigations involving various efficient techniques are being carried out to overcome this problem. This study presents the degradation of Congo red,an azo dye, using ultrasound and the degradation process was optimized by addition of ferum powder and salt or sodium chloride. Besides,adsorbent which was carbon paper also was used to enhance more degradation process.This method was called sonosorption method.The dye solution was subjected to ultrasound cleaner of 60 Hz at various initial concentrations,pH and temperature.The time set up for every sonication process was accurately thirty(30)minutes.The absorbance of Congo red dye before and after sonication process was analysed spectrometrically using UV-Vis Spectrophotometer to get the distinct values.The results showed that the initial dye concentration, pH and temperature of dye solution influenced the % decolourisation and lower initial values resulted in high % decolourisation. Additionally,the studies were carried out with addition of ferum powder and sodium chloride (salt) to increase the efficiency of Congo red degradation.The high concentration of salt and ferum powder that were both 2.0 M ended with high percentages of degradation,49.88 % and 96.42 % respectively.The sono-sorption method studies were conducted with presence of adsorbent(carbon paper)in the dye solution consequently means that the paper was put in the dye solution first before sonication started.The result came out positively compared with degrading of dye in absence of adsorbent.The outcomes of the present work indicate that ultrasound/Fe and sono-sorption method process are efficient for the degradation of Congo red in aqueous solution.